COVID-19 pandemic: Public attitudes and opinions on a global health crisis among residents in Sarawak, Malaysia - Wan Hashim, Wan Ibrahim; Thong, Jun Zhou; Lo, May Chiun; Abang Azlan, Mohamad; Ching, Jia Lie (Prime National Publishing Corp., 2023)
In Sarawak, Malaysia, several exceptional safety precautions and measures were adopted to prevent the outbreak of coronavirus disease 2019 (COVID-19) pandemic from spreading. Individuals’ attitudes and opinions have impact on their obedience toward control procedures. Sarawak residents’ attitudes and opinions toward COVID-19 were investigated in the present study. An online questionnaire developed using Google Forms was completed by 1,462 residents from all 12 divisions in Sarawak. The findings show that most Sarawak residents have positive attitudes and opinions about current standard operating procedures (SOPs) toward COVID-19. More than half of the respondents stand unbiased for the effectiveness of these SOPs, while most respondents have a neutral standpoint regarding the current law enforcement. The partial least square regression results found using the WarpPLS 7.0 software indicate that Sarawak residents’ attitudes, opinions about current SOPs, and their effectiveness are significantly linked to practices for the prevention of COVID-19 outbreak, whereas these residents’ opinions about current law enforcement were observed to have no significant relationship with proper practices for measures.